The politics of urban greening: an introduction. Issue 2 (2nd April 2020) - Cooke, Benjamin
ABSTRACT: Global enthusiasm for nature in cities is at high point. Australia is no exception, where there is a great deal of policy momentum and research interest in urban greening. The challenges presented by increasing urban heat associated with climate change, greater awareness of the potential social, physical and psychological benefits of exposure to ecologies for people, and recognition of cities as vital habitats for more-than-humans are central tenants of urban greening enthusiasm. Yet, there is a need for a more critical lens on urban greening in Australia. One that interrogates the purported normative, apolitical and instrumental benefits of greening, to position greening within a trajectory of the power relations, settler-colonialism, socio-ecological processes and capital flows that constitute the urban. This editorial introducing the special issue on urban greening politics explores how different conceptions of urban natures – green space, urban forestry and green infrastructure – have been put to work, before outlining the potential of 'urban greening' as the terminology for a more politically sensitive and process-orientated framing. The editorial concludes with a summary of the contributions to the special issue.